La Jeune Grecque de David d’Angers ou le rêve brisé - Philippe Durey (Les Cahiers de l'École du Louvre)
Little-known in France because of the secondary place of sculpture vis-à-vis painting in the cultural consciousness of the contemporary public concerning the nineteenth century, as well as because of the poor representation in the Louvre (as in most of the great fine art museums) of the works of David d’Angers, Reviving Greece nevertheless occupies a central place in French sculpture of the first half of the nineteenth century. While David d’Angers’ interest in Botzaris and the Greek cause, and the way he came up with his idea and his attachment to his statue are fairly well-documented, part of the history of this work has remained in the dark: the exact date of its execution, the knowledge of it in France before it was sent to Greece, the circumstances of its sending, the contacts with the Greeks, David’s place in the philhellenic movement, his sentimental and phantasmatic relationship with Greece, his plans to leave and set up a school of sculpture there, and finally the brutality of his disappointment in 1852. This article sheds new light on this work, which is of both historical and artistic interest not only because the fate of the statue recounts a moment in the relations between two countries, France and Greece, but also because of the failed – and perhaps impossible – transplantation of an already-established artist reveals the difficult, long and painful cultural journey of a young nation in the European concert of the time.